The Protective Effect of N-Acetylcysteine and Honey Against Lungs Damage of Mice (Mus Musculus) After Cigarette Smoke Exposure: A Histological Study - Yudhie Djuhastidar Tando; Yuniasih Mulyani Jubeline Taihuttu; Parningotan Yosi Silalahi; Zwesty Anggreany Salhuteru (Journal of Biomedicine and Translational Research, 2022)
Background: Cigarette smoke is a source of free radicals that could cause lung damage. Honey and N-Acetylcysteine have antioxidant effects that could play a role in preventing lung damage.Objective: This study aims to compare the effects of honey and N-Acetylcysteine on lung histological features of mice (Mus musculus) after exposure to cigarette smoke.Methods: This research is an actual experimental study with post-test only control group design. There were 25 adult male mice selected and divided into four groups, i.e., the standard control group (not given exposure or treatment); the negative control group (received 0.2 mL of aqua bidest and exposure to cigarette smoke); the first treatment group (received 0.2 ml of honey and exposure to cigarette smoke); the second treatment  group (received 0.2 mL of N-Acetylcysteine and exposure to cigarette smoke). The treatment was carried out every day for 21 days.Result: One way ANOVA statistical test showed significant differences between the experimental groups (p<0.001). Mice in the group that was only received aqua bidest (negative control group) had the highest percentage of lung damage (76.6%) compared to mice from other groups. The lowest percentage of lung damage was found in the treatment group that received NAC (26.6%). Tukey test showed no significant differences in the lung damage between honey and N-Acetylcysteine groups (p=0.685).Conclusion: Honey and N-Acetylcysteine demonstrated some protective effect against lung damage of mice as a result of cigarette smoking exposure. Further research is recommended by extending the treatment time, increasing the exposure to cigarettes smokes per day, as well as varying the dose of honey and N-Acetylcysteine administered